Bmal1 Regulates Macrophage Polarize Through Glycolytic Pathway in Alcoholic Liver Disease - Zhou, Yiwen; Wu, Meifei; Xu, Lei; Cheng, Jieling; Shen, Jie; Yang, Tianyu; Zhang, Lei (Frontiers in Pharmacology, 2021)
Hepatic macrophages play a critical role in inflammation caused by alcohol feeding. During this process, variation of macrophage phenotypes triggers inflammatory responses in a variety of ways. Moreover, there is increasing evidence that Brain and Muscle Arnt-Like Protein-1 (Bmal1) is regarded as a key regulator of macrophage transformation. In our study, Bmal1 was detected to be low expressed in EtOH-fed mice tissue samples and ethanol-induced RAW264.7 cells. After hepatic specific overexpression of Bmal1, M1 macrophage markers were evidently down-regulated, while M2 markers were on the contrary, showing an upward trend. Furthermore, alcoholic liver lesions were also improved in alcohol feeding mice with overexpressed Bmal1. On this basis, we also found that the glycolytic pathway can regulate macrophage polarization. In vitro, blocking of glycolytic pathway can significantly inhibit M1-type polarization. Importantly, glycolysis levels were also restrained after Bmal1 overexpression. What’s more, Bmal1 exerts a negative regulatory effect on glycolysis by interacting with S100A9 protein. Further studies showed that the alleviation of alcoholic liver disease (ALD) by Bmal1 was associated with glycolytic pathway suppression and M1 macrophage polarization. In summary, we demonstrated that Bmal1 is a gene capable of relieving ALD, and this effect may provide new insights for altering macrophage phenotypes to regulate inflammatory responses in ALD.